How can teachers engage students in online learning? A Conceptual Framework - Delipiter Lase; Zega, Trisa Genia Chrisantiana (Technium Social Sciences Journal, 2021)
This article discusses how to teachers ensure further learning - post-learning in the emergency of the Covid-19 pandemic can effectively increase student ownership and engagement in online learning. Most educational institutions’ closure resulted in a dramatic change in education, marked by the emergence of distinctive e-learning, where teaching was conducted remotely and on digital platforms. The transition in the education system impacts various stakeholders, especially teachers and students, in various ways. One of the issues surrounding students’ engagement in schools and the learning process became a hot topic again, considering that recently almost all countries in the world have been targeted by the spread of the global pandemic Covid-19. There is almost no learning process without the engagement and activeness of learners in the process itself. Students engaged in their learning are energized by curiosity, originality, and satisfying relationships, leading to better academic achievement. Through the theoretical review and content analysis, the authors explained that the ownership and engagement of learners in online learning could be achieved by combining several strategies. Teachers need to reflect on these strategies and how each falls into this area of engagement. Some teachers may be able to apply quickly and through relative ease, while others require wise planning. Teachers need to think of one of the strategies that teachers can immediately implement to engage students in their learning.